Biodiesel production from palm oil over monolithic KF/γ-Al2O3/honeycomb ceramic catalyst. (15th May 2015) - Gao, Lijing; Wang, Songcheng; Xu, Wei; Xiao, Guomin
Highlights: Honeycomb ceramic (HC) was used as monolithic catalyst support. KF/γ-Al2 O3 /HC monolithic catalyst used in the transesterification. Optima reaction condition in the fixed-bed reactor was studied. Oil conversion could exceed 96% under 140 °C and saturated vapor pressure. Abstract: During transesterification process in the fixed-bed reactor, traditional heterogeneous catalyst cannot stand the high pressure drop and would easily breaks at the reactor bottom thus blocking the outlets. KF/γ-Al2 O3 /honeycomb ceramic (HC) monolithic catalyst which was prepared in this research can be utilized because of its thermal and mechanical stability. γ-Al2 O3 was deposited on the inert HC surface as a second carrier and KF acted as an active component. Loading ratio and loading intensity were both examined in order to select for catalyst with best catalytic performance. Optima reaction condition in the fixed-bed reactor was studied by investigating the effect of residence time, methanol/oil molar ratio and reaction temperature on oil conversion. Experiment results indicated that when the residence time was 33 min, the methanol/oil molar ratio was 18:1, the reaction temperature was 140 °C and with saturated vapor pressure, oil conversion could exceed 96%. X-ray diffraction (XRD) and scanning electron microscope (SEM) indicated that the KF/γ-Al2 O3 /HC monolithic catalyst shared the same alkaline catalytic centers identical to KF/γ-Al2 O3 .